Correlation between Foreign Direct Investment and Economic Growth in Nepal - Gautam, Subas (Academia Research Journal, 2024)
Nepal's strategic location between India and China, coupled with favorable market access and lower tariffs, presents an enticing prospect for foreign investors. Despite these advantages, the nation faces challenges, including a fragile financial sector, bureaucratic hurdles, and political instability, hindering substantial Foreign Direct Investment (FDI). This study investigates the correlation between FDI and economic growth in Nepal, recognizing the critical role of FDI in the country's development. The goal of the study is to examine the linear relationship between these factors while analyzing the trajectory and structure of foreign direct investment and economic growth in Nepal. Among the specific goals are looking at FDI inflow by sector, assessing the link between FDI and economic growth, and developing theories based on these goals. The research design is explorative, descriptive, and analytical, employing time series data from FY 1994 to 2021. Data is sourced from government bodies like NRB, MOF, MOI, and CBS, and econometric tools are applied for analysis. Limitations include reliance on secondary data and a study period of 25 years. The study underscores the need for an investor-friendly environment to attract foreign investments and addresses the challenge of accumulating capital domestically. Recognizing the indispensable role of FDI in Nepal's economic development, the study provides insights for policymakers and recommends investment-friendly policies to promote FDI inflows and contribute to economic growth.